A Corpus-Based Analysis of Modal Auxiliaries of William Golding’s Novel “The Lord of Flies” - Nada, Anwar; Ajwan, Alkadr (Journal International of Lingua and Technology, 2023)
This study aimed to identify the types of modal auxiliaries and the meanings of modal auxiliaries in the novel The Lord of Flies by William Golding. This study uses mixed methods. First, this study used corpus-based quantitative data to obtain modal auxiliary in The Lord of Flies novel examined by looking at the concordance and frequency of the Ant Conc software tools. Second, the data analysis process used qualitative methods to show the function or meaning of the modal auxiliary verbs in The Lord of Flies novel. Based on data analysis, it shows that there are 549 modal auxiliary verbs in The Lord of Flies novel divided into 9 types of modals, namely the modal could with an occurrence frequency of 161 times (24.49%), the modal can with an occurrence frequency of 136 times (24.91%), the modal would appear with a frequency of 111 times (20.33%), the modal might appear with a frequency of 41 times (7.69%), the modal must appear with a frequency of 37 times (6.78%), the modal should appear with a frequency of 22 times (4.03%), the modal will appear with a frequency of 15 times (2.75%), the modal may appear with a frequency of 14 times (2.56%), and the modal shall appear with a frequency of 8 times (1.47%). And the meanings of modal auxiliary verbs in The Lord of Flies novel are intentional, epistemic, deontic, and dynamic meanings.